Foreign Aid in Nepal - Pandey, Kiran Bahadur (Economic Journal of Development Issues, 2018)
Foreign aid is essential for least developed countries like Nepal because these countries have the shortage of fund to meet their domestic investment for accelerating economic development and also to finance the import of essential capital goods required for the development. Nepal receives foreign aid from bilateral and multilateral sources. Following a descriptive approaches this paper analyses the trend of foreign did flow in Nepal from aggregative perspective. Economic Journal of Development Issues Vol. 23&24 No. 1-2, (2017) Combined Issue, Page : 71-76